ANALISIS KEMAMPUAN REPRESENTASI VERBAL MATEMATIS SISWA DALAM MENYELESAIKAN SOAL OPEN ENDED PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DI FASE E 4 SMA N 8 KOTA JAMBI - Mersiana Mersiana; Sri Dewi; Eni Defitriani (PHI: Jurnal Pendidikan Matematika, 2025)
This research is motivated by the low verbal representation ability of students of SMA N 8 Jambi City. The purpose of this research is to analyze students' mathematical verbal representation ability in solving open-ended problems on the material of Two-Variable Linear Equation Systems in phase E 4 of SMA N 8 Jambi City. This research uses a descriptive method with a qualitative approach.. The instruments used in this study were a test of mathematical verbal representation ability in solving open-ended type problems and interviews. Data analysis techniques were carried out by reducing data, presenting data, and drawing conclusions. Checking the validity of the data used triangulation techniques. The results of the study showed that students' verbal representation in solving open- ended problems, with representative subjects of students with high, medium and low abilities. Subjects S1 and S2 who have high verbal representation ability, tend to be more able to understand the problems from the questions and are able to show 3 (three) indicators of verbal representation ability, namely mathematical concepts, organization of ideas and expressions, while subjects S3 and S4 who have a moderate level of verbal representation ability show that the subjects are able to take the information in the questions and are able to show 2 (two) aspects of mathematical ability, namely mathematical concepts and organization of ideas. Meanwhile, subjects S5 and S6 who have a low level of verbal representation ability are not able to take information from the questions and can only show 1 (one) indicator, namely mathematical concepts.